Kyoto and the heavens: setting Japan's center of time. Issue 4 (2nd October 2019) - Frumer, Yulia
Abstract: Why did scholars in mid-nineteenth century Japan assume that the prime meridian should run through Kyoto – positioning the city not only as the center of Japan but also of the entire world? Tracing the close connections between longitude determination, astronomical time measurement, and calendar compilation, this article argues that the making of Kyoto-centered place was rooted in the use of astronomical time as a tool for analyzing celestial and geographical space . This article first shows that the existence of a prime meridian on Japanese maps was the result of astronomical timekeeping practices used by an early nineteenth-century surveyor, Inō Tadataka. It then traces the decision to draw the prime meridian specifically through Kyoto to various centuries-old calendrical conventions, the astronomical work of Shibukawa Shunkai, and the metaphysics of seventeenth-century philosopher Yamazaki Ansai. The article emphasizes the role that practices of measurement, calculation, and observation played in the shaping of a map, the appearance of which eventually manifested the idea of the place it purportedly represents.